Funder's meaning making regarding complex, adaptive projects: Findings from a developmentally oriented feasibility study. Issue 2 (16th October 2018) - Jones, Jennifer A.; Daniel, David L.
Abstract : Environmental non‐profit organizations need to raise billions of dollars in the coming years to support climate change initiatives. Many of these initiatives are complex in nature and markedly different from traditional environmental projects such as land conservation. These interventions are dependent on sufficient funding, and sufficient funding is dependent upon whether donors understand the problem and the intervention. Understanding the nature of complex problems is related to what developmental theorists call an individual's developmental level. Using a qualitative case study methodology, we conducted interviews with donors from one chapter of a large environmental organization, The Nature Conservancy, to (a) determine how high‐level donors react to capital campaign materials presenting systems‐oriented interventions and (b) test the utility of a developmentally informed feasibility study interview. The findings indicate that a developmental approach to feasibility study interviews is useful. Donors expressed interest about the idea of systemic change but are unclear as to how to measure the success of complex, adaptive initiatives. The developmentally informed interview process deepened the conversations between donors and staff and to provide what many interviewees described as a rare and much‐needed opportunity for reflection. Although the results from a single case study are not generalizable, the study nevertheless makes a theoretical contribution and has practical implications for fundraisers of organizations addressing climate change and, potentially, other complex issues.